Let 4x = 15 - 5y or x = 15/4 - 5/4 y
substitute that in the other equation for x:
6(15/4 -5/4 y) - 4y = 11
90/4 - 30/4 y - 16/4 y = 44 /4
- (30/4 + 16/4) y = 44/4 - 90/4
-46/4 y = -46/4
y =1
then substitute y =1 into either equation:
4x + 5 = 15
4x = 10
x = 2.5
Check by substituting the x and y into the other equation:
6 (2.5) - 4 = 11
15 = 15
so (2.5, 1) is the solution
2007-09-15 12:34:25
·
answer #1
·
answered by spongeworthy_us 6
·
1⤊
2⤋
4x + 5y = 15 5y = 15 - 4x y = 3 - 0.8x Substituting in 3 - 0.8x for y in the two of the two equations (i'm going to compliment 6x - 4y = 11): 6x - 4y = 11 6x - 4(3 - 0.8x) = 11 6x - 12 + 3.2x = 11 9.2x - 12 = 11 9.2x = 23 x = 23/9.2 x = 2.5 (aka 5/2) for this reason 6(2.5) - 4y = 11 15 - 4y = 11 -4y = 11 - 15 -4y = -4 y = a million So x = 5/2, y = a million EDIT: the different answer is incorrect from the get-circulate, because of the fact he/she forgot to alter in (-5y + 15) / 3 quite of -5y + 15 for x. additionally, in case you plug interior the x and y values from the different answer, you don't get returned the values on the superb-hand facet of the two equations which you're meant to. in the previous you fee down an answer, verify your man or woman first.
2016-11-15 08:07:55
·
answer #2
·
answered by ? 4
·
0⤊
0⤋
4x+5y=15 and 6x-4y=11
There are different ways that you can do this and arrive at the same answer, but here's one of them:
Multiply the first equation by 4, and the second equation by 5
4x+5y=15 and 6x-4y=11 ---> 4(4x+5y=15) and 5(6x-4y=11)
---> 16x+20y=60 and 30x-20y=55
Add the two equations together, adding like parts.
16x+20y=60 and 30x-20y=55 ---> 46x=115 (20y and -20y cancelled out)
Divide by 46 on both sides.
46x=115 --> x=2.5
Now plug in 2.5 for x in one of the equations to get y. Using the first original equation:
4x+5y=15 ---> 4(2.5)+5y=15 ---> 10+5y=15
Subtract 10 from both sides
10+5y=15 --> 5y=5
Divide by 5.
5y=5 --> y=1
So x=2.5 and y=1
2007-09-15 12:45:27
·
answer #3
·
answered by Aquamarina 3
·
1⤊
1⤋
Multiply the first equation by 1.5 and subtract from second equation to eliminate the x term:
1.5*4x=6x, 1.5*5y=7.5y, 1.5*15=22.5 SO
6x - 4y - 6x -7.5y=11 - 22.5
-11.5y = -11.5 => y = 1 => 4x+5(1)=15
4x=15-5=10 => x = 2.5
2007-09-15 12:38:32
·
answer #4
·
answered by oldschool 7
·
1⤊
1⤋
4x + 5y = 15
4x = 5(3-y)
x = 5/4(3-y) . . . . multiply both sides by 6
6x = 30/4(3-y) = 15/2(3-y) . . . . substitute to 2nd equation
6x - 4y = 11
15/2(3-y) - 4y = 11 . . . . multiply both side by 2
15(3-y) - 8y = 22
45 - 15 y - 8y = 22
23y = 23
y = 1
x = 5/4(3-y) = 5/2
2007-09-15 12:36:16
·
answer #5
·
answered by CPUcate 6
·
0⤊
2⤋
16x + 20y = 60
30x - 20y = 55-------ADD
46x = 115
x = 115 / 46
x = 2½
10 + 5y = 15
5y = 5
y = 1
x = 2 ½ , y = 1
2007-09-15 20:25:29
·
answer #6
·
answered by Como 7
·
2⤊
0⤋
4x+5y=15 //Multiply equation by 6
6x-4y=11 //Multiply equation by 4
24x+30y=90
24x-16y=44 //24x-24x+30y+16y=90-44
46y=46
y=1
//Now substitute y=1 into both equations:
4x+5=15
4x = 10
x=2.5
6x-4=11
6x=15
x=2.5
y=1
x=2.5
2007-09-15 12:38:55
·
answer #7
·
answered by Spectator 3
·
1⤊
1⤋